DEVELOPING MODUL OF MICROBIOLOGY SUBJECT THROUGH BIODEGRADATION BY USING THE POTENCIAL OF INDIGEN BACTERIA - Hasminar Rachman Fidiastuti; Kardiana Metha Rozhana (University of Muhammadiyah Malang, 2016)
Students in the study of science, need to pay attention to the nature of science. Science studied to develop the ability to think (minds on), skills (hands on) as well as the scientific attitude (heart on). Study Microbiology in Prodi TIP, University Tibhuwana Tunggadewi is about microorganisms. The writers conducted research related to environmental remediation efforts to harness the potential of bacteria indigen as an agent in the process of biodegradation. Research results are used as a reference in the preparation of the module. Through modules made based on the results of research, students are expected to develop 1) the ability to think that microorganisms can become agents in the process of rehabilitation of environmental pollution and can be isolated from the waste, develop 2) skills through practical biodegradation, and develop 3) attitudes scientific through concept which have been studied, in providing practical solutions to the problems of environmental pollution. The module aims to improve the efficiency and effectiveness of learning in the classroom either time, funds, facilities or personnel to obtain maximum results. Application of Microbiology learning which refers to the fusion module and science process skills through implementation of practical activities, is expected to be an alternative to creating a learning Microbiology which refers to aspects of the process, product and scientific attitude. The result is already done three stage preparation of teaching materials in the form of Microbiology module which refers to the model of research and development model of the 4-D (Thiagarajan, et al), includes define, design, and development. Results at the stage of defining the characteristics of students' analysis, task analysis, analysis of the concept and analysis of learning objectives. At the design stage to do the design and materials development, followed by the development phase, ie measurement of the feasibility of the modules have been prepared. Results obtained to measure the feasibility of the module is the achievement level of 85% by the expert development of teaching materials, 87% by material experts and 84% by the practitioner. The average yield of legibility student questionnaire amounted to 86.55%. The results of this validation consulted in order to repair the module. Keywords: Biodegradation in vitro, tanning pollutants, indigen bacteri